Youth in Transition: Exploring a life course perspective on leaving Care in Africa - Kelly, B.; Breda, A.V.; Frimpng-Manso, K.; et al. (Youth & Society, 2023)
While there is a substantial body of leaving care research, the theorization of care leaving has been more limited. Only a few studies have incorporated a life course perspective, mainly in Global North contexts where life course perspectives may differ significantly from those in the Global South, including Africa. Drawing on findings from a feasibility research study, this paper contributes to the emerging international literature on theorizing care leaving by applying a life course perspective to the experiences of youth leaving care in four African countries. The paper highlights how life course can be a useful conceptual framework for understanding the experiences of care leavers with an emphasis on four core concepts: biography, linked lives, waithood, and agency. Implications for policy and practice are outlined with a focus on interdependence, participatory practice, biography, and cultural transition planning alongside efforts to redress systemic, oppressive barriers facing care leavers in society.
Research Article
Keywords: life course; youth transition; leaving care; waithood